The concept of power and its geographical analysis (Journal of the College of Basic Education, 2022)
The research dealt with the study of the concept of power and its geographical analysis in terms of the concept of power and the development of this concept through the time stages. It also dealt with the definition of power as well as the equations for measuring the power of the state.